Aviation cybersecurity : foundations, principles, and applications - Song, Houbing; Hopkinson, Kenneth; De Cola, Tomaso; Alexandrovich, Tom; Liu, Dahai (Radar, Sonar and Navigation, 2021)
The interdisciplinary nature of aviation cybersecurity and its wide-ranging impact requires contributions of expertise from multiple disciplines to collaborate in identifying ways forward. This book provides an understanding of the key technical, social and legal issues in aviation cybersecurity, and proposes innovative solutions